2010
DOI: 10.1007/s12224-010-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Hemiparasitic Species Rhinanthus minor with its Host Plant Community at Two Nutrient Levels

Abstract: For root hemiparasites, host plants are both the source of water and nutrients below-ground, but competitors for light above-ground. Hemiparasites can reduce host biomass, and in this way considerably affect the whole plant community. To investigate these effects, we carried out two experiments in an oligotrophic meadow with a native population of Rhinanthus minor. In the first experiment, removal of R. minor was combined with fertilization in a factorial design, and in the second one, we manipulated R. minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 43 publications
(74 reference statements)
9
61
0
Order By: Relevance
“…Anecdotal observations (Henderson 2002) and results from greenhouse and mesocosm experiments (Matthies 1995;Bardgett et al 2006) and manipulative Weld studies (Marvier 1998;Joshi et al 2000;Mudrák and Lepn 2010) indicate that hemiparasites can strongly limit host growth and may exert keystone eVects in nutrient-poor, high-light environments (Press and Phoenix 2005;Bardgett et al 2006). Matthies (1995) hypothesized that eVects on community productivity and diversity arise because these green plants are poor competitors for light but strong parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal observations (Henderson 2002) and results from greenhouse and mesocosm experiments (Matthies 1995;Bardgett et al 2006) and manipulative Weld studies (Marvier 1998;Joshi et al 2000;Mudrák and Lepn 2010) indicate that hemiparasites can strongly limit host growth and may exert keystone eVects in nutrient-poor, high-light environments (Press and Phoenix 2005;Bardgett et al 2006). Matthies (1995) hypothesized that eVects on community productivity and diversity arise because these green plants are poor competitors for light but strong parasites.…”
Section: Introductionmentioning
confidence: 99%
“…For parasitism to alter diversity, host species must diVer in resistance to or tolerance of parasitism (Press and Phoenix 2005). Grasses appear to be particularly susceptible to parasitism (Marvier 1998;Joshi et al 2000;Cameron et al 2006;Mudrák and Lepn 2010). Greater depression in the growth of these usually dominant species by hemiparasites may relax competition with forbs and increase abundance and diversity of the latter group.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hwangbo and Seel (2002) suggest that light availability does not affect the growth of Rhinanthus minor L. Also, it has been proposed that, after establishment, sward density is not important for the persistence of Rhinanthus (de Hullu et al 1985). On the contrary, Mudrák and Lepš (2010) found that the mortality of Rhinanthus minor L. was higher in fertilized (and so more productive) plots. Unlike in the model by Smith (2000), it is not possible for hemiparasites to outcompete the host species (neither in reality, nor in our model).…”
Section: Discussionmentioning
confidence: 87%
“…6), and with our own field experience. Similarly, fertilizing and higher host community biomass lead to decreased seedling survival (Mudrák and Lepš 2010), decreased fruiting (van Hulst et al 1987) and density of hemiparasites (Westbury and Dunnett 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although a thinning experiment would be required to draw a complete picture of competitive relationships among M. pratense individuals, the present data clearly suggest presence of density dependence in its populations. The intraspecific competition however appears to act by an increase of mortality rather than by decrease of plant growth rate, which was also observed in populations of other hemiparasites, Rhinanthus minor (Mudrák & Lepš 2010) and R. angustifolius (de Hullu et al 1985). This effect of competition can be hypothesized to be related with lack of resource storage organs; instead, the resources are rapidly invested into growth (or reproduction) in these hemiparasites.…”
Section: Survival and Growthmentioning
confidence: 87%